Isolation and Characterization of primary human trabecular meshwork cells from segmental flow regions: New tools for understanding segmental flow. (August 2020) - Staverosky, Julia; Dhamodaran, Kamesh; Acott, Ted; Raghunathan, VijayKrishna; Vranka, Janice
Abstract: Segmental flow in the human trabecular meshwork is a well-documented phenomenon but in depth mechanistic investigations of high flow (HF) and low flow (LF) regions are restricted due to the small amount of tissue available from a single donor. To address this issue we have generated and characterized multiple paired HF and LF cell strains. Here paired HF and LF cell strains were generated from single donors. Cells were characterized for growth and proliferation, as well as gene and protein expression of potential segmental region markers. Cells isolated from HF and LF regions have similar growth and proliferation rates. Gene expression data reveals vascular cell adhesion protein 1 (VCAM1), thrombospondin 2 (THBS2), and tissue inhibitor of metalloproteinase 1 (TIMP1) are potential markers of LF cells in vitro . Protein expression of VCAM1, THBS2 and TIMP1 are complex and may reflect the dynamic nature of the TM. Initial protein expression levels of these genes is either similar between HF and LF cells (VCAM1, THBS2), or higher in HF compared to LF in some strains (TIMP1). However, after long term culture LF cells express higher levels of VCAM1, TIMP1 and THBS2 protein compared to HF cells. HF and LF cell strains are a powerful new tool that enable understanding segmental flow allowing for multiple experiments on the same genetic background. Highlights: Here we generate novel cell strains from segmental regions of human TM tissues. High flow and low flow cell strains have similar growth and proliferation rates. THBS2, VCAM1, and TIMP1 are potential low flow cell markers. Low flow cell markers may be useful for developing targeted therapeutics.